Визначення програм нагріву в установках індукційного зонного нагріву металевих заготовок - Солодкий, Д. Є. (ХНУРЕ, 2021)
The algorithm can be applied for the case when inductors dimensions and distance between are known, and under the assumption that inductors powers are constant over time. The obtained values can be used as a guideline for choosing the power of inductors in the design and operation of heating complex.
Keywords: металеві заготовки; індукційний зонний нагрів